2019
DOI: 10.1096/fj.201901466r
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of gpr27 alters acylcarnitine metabolism, insulin sensitivity, and glucose homeostasis in zebrafish

Abstract: G protein-coupled receptors (GPCRs) comprise the largest group of membrane receptors in eukaryotic genomes and collectively they regulate nearly all cellular processes.Despite the widely recognized importance of this class of proteins, many GPCRs remain understudied. G protein-coupled receptor 27 (Gpr27) is an orphan GPCR that displays high conservation during vertebrate evolution. Although, GPR27 is known to be expressed in tissues that regulate metabolism including the pancreas, skeletal muscle, and adipose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…None of these genes had a highly conserved non-synonymous variant that is expected to be damaging. Foxp1 has previously been shown to regulate hepatic glucose homeostasis 45 , and insulin stimulated glucose uptake 46 , making it a strong candidate, although both Gpr27 47 , 48 and Prok2 49 also play a role in glucose related phenotypes.
Figure 7 Genome scans for select intermediary serum biochemistry measures.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these genes had a highly conserved non-synonymous variant that is expected to be damaging. Foxp1 has previously been shown to regulate hepatic glucose homeostasis 45 , and insulin stimulated glucose uptake 46 , making it a strong candidate, although both Gpr27 47 , 48 and Prok2 49 also play a role in glucose related phenotypes.
Figure 7 Genome scans for select intermediary serum biochemistry measures.
…”
Section: Resultsmentioning
confidence: 99%
“…Although no variants were found in Foxp1 , this gene falls directly under the peak marker and Foxp1 has been shown to regulate hepatic glucose homeostasis 45 and insulin stimulated glucose uptake 46 . Both Gpr27 47 , 48 and Prok2 49 , which fall within the wider confidence interval are also potential candidates within this region. No significant associations were observed for serum creatinine and BUN.…”
Section: Discussionmentioning
confidence: 99%
“…The fish did not show high FBS with normal diet, but a significant increase with a high fat diet, as we see in human T2DM state. The fish were also resistant to insulin injection, suggesting insulin resistance condition and a solid model for subsequent studies of T2DM (Nath et al, 2020 ).…”
Section: Methods/models Of Inducing Hyperglycemia In Zebrafishmentioning
confidence: 99%
“…In human, high fasting blood glucose is usually the first indicator of T2DM existence and a clue to further investigations. In the reviewed studies, fasting blood glucose elevation (Gleeson et al, 2007 ; Connaughton et al, 2016 ), post-high content diet feeding blood glucose elevation (Yang et al, 2018 ), post-prandial glucose elevation (Nath et al, 2020 ), or whole larval glucose elevation (Karanth et al, 2016 ) are reported as the primary indicator of T2DM existence possibility.…”
Section: Methods Of Model Verificationmentioning
confidence: 99%
“…In addition, the expression pattern of these genes appear to be comparable to humans. 37 38 39 40 41 One important differences in lipid metabolism between zebrafish and humans is that zebrafish only produces full-length apoB (apoB-100) and lack truncated apoB (apoB-48). Therefore, despite their structural similarity to humans, zebrafish chylomicrons are coated with apoB-100 which renders them less likely to undergo rapid clearance by the liver and mature as LDL.…”
Section: Lipid Metabolism In Zebrafish and Humansmentioning
confidence: 99%